Analisis Strategi Pembelajaran Dalam Meningkatkan Kemampuan Pemahaman Dan Aplikasi Konsep - Muhammad Aniur Rofiq; Agus Irfan; Dimas Pratama; Miftahus Surur; Nur Azizah (CV. Aksara Global, 2024)
An effective learning process in the classroom involves increasing the ability to understand and apply concepts. Learning strategies play a crucial role in realizing this goal, becoming the main focus in efforts to improve the quality of education. The goals of modern education involve developing the ability to understand and apply concepts, producing individuals who are not only skilled in knowledge but also able to apply these skills in everyday life. In addition, the application of knowledge becomes essential, where learning is not only about receiving information but also about the ability to apply knowledge in real contexts. Learning strategies that focus on application help students develop practical skills that can be used in a variety of situations. Analysis of learning strategies is carried out by considering their relevance to the curriculum and support for learning styles. Relevant research results from 12 articles have been analyzed to gain an in-depth understanding of the most effective learning strategies. Based on the results of the analysis, several learning models such as Conceptual Understanding Procedures, Teams Games Tournament, and Blended Learning have been proven to be effective in increasing concept understanding. This research highlights the role of learning strategies in improving the ability to understand and apply concepts at the educational level.